2021
DOI: 10.1017/s1754470x21000222
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision in CBT training: what do participants view as effective?

Abstract: Literature pertaining to cognitive behavioural therapy (CBT) supervision is limited, particularly about CBT supervision during training. This exploratory study outlines the thoughts of supervisors and supervisees in a training context about which elements make supervision effective. Four supervisees and four experienced CBT supervisors (all from a CBT training programme and independent of one another) were interviewed and asked to consider what makes CBT supervision during training effective. Their responses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 42 publications
1
11
0
2
Order By: Relevance
“…This finding is consistent with theory and research supporting the use of multiple teaching methods in promoting trainee satisfaction and better learning outcomes (e.g. Kelly and Hassett, 2021; Milne et al ., 2003; Murr et al ., 2020; Newman, 2013; Prasko et al ., 2012).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is consistent with theory and research supporting the use of multiple teaching methods in promoting trainee satisfaction and better learning outcomes (e.g. Kelly and Hassett, 2021; Milne et al ., 2003; Murr et al ., 2020; Newman, 2013; Prasko et al ., 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have reported strategies that trainees deem useful (e.g. Kelly and Hassett, 2021; Murr et al ., 2020), but research examining trainee perspectives remains inadequate, and no firm conclusions can be made about what trainees want from supervision (Callahan and Love, 2020; Kelly and Hassett, 2021). Therefore, this study aimed to further explore what trainees believe is most and least helpful following each supervision meeting, and to determine whether trainees’ perceptions of helpful supervision interventions align with what the expert consensus purports to be effective CBT supervision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first UK‐based IPA study that sought to capture the lived experiences of CBT supervisors and supervisees. Given the seismic effects that IAPT has had on CBT provision, training and culture since its inception (Kelly & Hassett, 2021; Liness et al, 2019; Liness & Muston, 2011; Turpin & Wheeler, 2011), the aim was to gauge CBT supervisor and supervisee experiences and explore how they made meaning of supervision (Smith et al, 2009). Previous research sampling the routine use of supervision took place pre‐IAPT (e.g., Townend et al, 2002) and had indicated that CBT practitioners rarely use active supervision methods.…”
Section: Discussionmentioning
confidence: 99%
“…At face value, CBT supervision shares many of the structural features of CBT treatment (Armstrong & Freeston, 2006; Kelly & Hassett, 2021; Prasko et al, 2012). For example, according to expert consensus within the field, it is recommended that supervision has an agreed agenda, specific task focus and review of learning, which mirrors the format of a therapy session (Gordon, 2012; Pretorius, 2006).…”
Section: Introductionmentioning
confidence: 99%